THE HIDDEN ECONOMIC BURDEN OF LEPTOSPIROSIS: HEALTHCARE COSTS AND PATIENT IMPACT - Nugraheni, Wahyu Pudji; Lestyoningrum, Sinta Dewi; Pawitaningtyas, Indah; Nuraini, Syarifah; Putri, Linta Meyla; Ristiyanto; Milcent, Carine (Universitas Airlangga, 2025)
Background: Leptospirosis is a public health issue caused by the Leptospira bacterium, leading to significant economic impacts. The cost of illness due to Leptospirosis encompasses hidden costs that significantly affect individuals and society Aims: This study aimed to assess the hidden economic burden (direct and indirect costs) experienced by patients and their families due to healthcare treatment of leptospirosis. Methods: This descriptive cross-sectional study was conducted in Banyumas Regency from February to June 2024. Data were collected from patients who completed leptospirosis treatment in 2023. The variables of cost were categorized into direct treatment cost, treatment cost, and indirect cost, which were analyzed descriptively. Results: Most leptospirosis patients were male, aged 26 – 45 years old, and the majority worked as farmers. Our study reveals that uninsured patients incurred higher out-of-pocket expenses during leptospirosis’ treatment. The productivity loss was estimated at USD 44.75, with significant hidden costs being transportation (USD 31.90), caregiver support (USD 86.38), and hospital treatment (USD 231.40). Conclusion: The significant burden of Leptospirosis in Indonesia highlights the economic impact on individuals and the challenges within the healthcare system. This study calls for enhanced public health strategies focused on prevention, early diagnosis, and improved healthcare access to address the leptospirosis burden effectively. Keywords: Cost of illness, economic burden, financial impact, leptospirosis, productivity loss